EMPOWERMENT OF KAMPUNG UNGGUL BALITBANGTAN (KUB) CHICKEN FARMERS THROUGH THE OPTIMIZATION OF MANAGEMENT, SELF-MIXED FEED, FINANCIAL RECORDING, AND DIGITAL MARKETING IN TASIKMALAYA REGENCY - Frasiska, Nurul; Rahwana, Kusuma Agdhi; Fadilah, Mohamad Fazar (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program aims to improve the capacity of the Singaparna Free-Range Chicken Farmers Association (APAKSI) in production, business management, and marketing. Partners' primary challenges include dependence on manufactured feed, inefficient financial records, and limited market access and brand legality. The implementation method involves five stages: outreach, training, technology implementation, mentoring, and evaluation. As of this progress report, five of the eight planned visits have been conducted. Results include improved understanding of KUB chicken farming, the ability to independently produce fermented bran-based feed, the implementation of simple financial records, and the development of a brand logo to support marketing. Initial impacts indicate increased production efficiency, business management awareness, and farmer motivation to expand markets through e-commerce. With three remaining mentoring visits, the program's final targets are brand legality through PDKI, streamlined financial reporting, and active digital marketing.